Branding Melaka as a Complete Green City for State Image Enhancement - Chew, B.C.; Hamid, S.R.; Sukri, F.H. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
The Melaka state government is embarking its vision towards Green City (GC) state by 2020. However, Melaka faces several related sustainable issues such as traffic, public transportation, health problems and others that are big challenges for the Melaka state to implement a complete Green City Branding (GCB). This study was to examine the factors that influence Melaka state towards a complete GCB and to investigate strategies of Melaka state towards a complete GCB. A qualitative approach was utilized by conducting a case study at the Melaka Green Technology Corporation (MGTC) and a semi-structured in-depth interview session was done among fifteen executives to obtain the primary data. Thus, by preventing the Melaka state from being harmed, the benefits of embarking on a complete GCB may be beneficial to the social and economic well-being for the sake of current and future generations. Future studies should be focusing on the hurdles faced by the Melaka state government in implementing a complete GCB because the state government is serious in aiming for the Green City State status.